2008
DOI: 10.1063/1.2836266
|View full text |Cite
|
Sign up to set email alerts
|

High-performance polymer heterojunction solar cells of a polysilafluorene derivative

Abstract: High-performance polymer heterojunction solar cells fabricated from an alternating copolymer of 2,7-silafluorene (SiF) and 4,7-di(2′-thienyl)-2,1,3-benzothiadiazole (DBT) (PSiF-DBT) as the electron donor blended with [6,6]-phenyl-C61-butyric acid methyl ester as the electron acceptor were investigated. A power-conversion efficiency up to 5.4% with an open-circuit voltage of 0.90V, a short-circuit current of 9.5mAcm−2, and a fill factor of 50.7% was achieved under the illumination of AM 1.5G from a calibrated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
401
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(411 citation statements)
references
References 22 publications
7
401
2
1
Order By: Relevance
“…4 Along these lines, several other donor-acceptor low bandgap copolymers based on benzothiadiazoles have been synthesized. 5 Among them, some copolymers have been synthesized by using fluorenes, 6,7 carbazoles, 8,9 or dibenzosiloles 10,11 as electron-donating comonomers. Usually, with such bridged phenylene units, two thiophene units had to be added on both ends of the benzothiadiazole core to obtain relatively planar copolymers; such a coplanar structure should allow good charge transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…4 Along these lines, several other donor-acceptor low bandgap copolymers based on benzothiadiazoles have been synthesized. 5 Among them, some copolymers have been synthesized by using fluorenes, 6,7 carbazoles, 8,9 or dibenzosiloles 10,11 as electron-donating comonomers. Usually, with such bridged phenylene units, two thiophene units had to be added on both ends of the benzothiadiazole core to obtain relatively planar copolymers; such a coplanar structure should allow good charge transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…We selected a set of 50 training molecules compiled from the literature. 46,50,51,[111][112][113][114][115][116][117][118][119][120][121] These molecules include aliphatic side chains used to control packing structures. The current work is concerned with donor materials of BHJ design, but this method can naturally be applied to other device architectures and materials given the appropriate training set.…”
Section: Descriptor Model and Training Set Resultsmentioning
confidence: 99%
“…49 Following a similar technique, Wang et al replaced the fluorene moiety with silafluorene (SiF), and obtained a PCE of 5.4%. 50 The higher efficiency is a result of the broader absorption spectrum of silafluorene, which allows for a J sc of 9.5 mA/cm 2 .…”
Section: Organic Photovoltaic Materialsmentioning
confidence: 99%
“…This suggests that the interaction between the polymer chains in the solid state is strengthened through two-dimensional aggregation, which is consistent with this group's previous study and Yong Cao et al's study that indicated the result of an effective intermolecular interaction between polymeric backbones based on the regular arrangement formed by molecules in the process of developing films. 30,35,37,38 In addition to the red-shift in the UV-vis spectra of the film state compared with the solution state for PBDTAFQ, the π-π* transition intensity also decreased significantly (ca. 30%) when compared with the ICT absorption intensity.…”
Section: Optical-electrochemical Propertiesmentioning
confidence: 99%
“…The absorption peak in the high-energy region between 300 and 400 nm is based on localized π-π* transitions, 35 and the peak in the long wavelength region between 450 and 700 nm is based on the ICT between the polymer's acceptor and donor units. 36 PBDTAQ's λ max in the solution state was at 393 and 518 nm each, whereas PBDTAFQ's λ max was at 421 and 562 nm.…”
Section: Optical-electrochemical Propertiesmentioning
confidence: 99%